A global systematic review, meta-analysis and health risk assessment on the quantity of Malathion, Diazinon and Chlorpyrifos in Vegetables. (May 2021) - Kermani, Majid; Dowlati, Mohsen; Gholami, Mitra; Sobhi, Hamid Reza; Azari, Ali; Esrafili, Ali; Yeganeh, Mojtaba; Ghaffari, Hamid Reza
Abstract: It is widely believed that an increasing trend in the production and consumption of vegetables has led to a dramatic rise in the use of pesticides potentially threatening the health of consumers around the world. This systematic study along with meta-analysis has mainly centered on the evaluation of the quantity of three well-known pesticides namely, Malathion (MLT), Diazinon (DZN) and Chlorpyrifos (CPF) in vegetables. In this regard, a comprehensive literature search has been performed over the last decade (January 1, 2011 to June 21, 2020) within the scientific databases including PubMed, Web of Science, and Scopus. Of 1239 articles identified through the database screening, 22 plus 37 data report were retained and included in the meta-analysis phase. Additionally, the probabilistic human health risks for the consumers due to the intake of CPF, DZN and MLT from eating vegetables were estimated by the Monte Carlo Simulated (MCS) method. According to the findings, the maximum quantities of MLT, DZN and CPF in the vegetables were observed in Pakistan (222 μg/kg, 95%CI = 214.94–229.08), Thailand (245.00, 95% CI = 235.2–254.8) and South Korea (440 μg/kg, 95% CI = 437.19–442.81), while the lowest concentration levels were reported in China (1.7 μg/kg, 95% CI = 1.56–1.84), Poland (0.57, 95% CI = 0.46–0.68) and Poland (5.78 μg/kg, 95% CI = 4.40–7.12), respectively. The results of the Egger's and the Begg's tests revealed that no bias with regard to the potential publication was observed. Finally, non-carcinogenic risk assessment results demonstrated that the exposure to the studied pesticides thorough vegetables consumption could not threaten the health of consumers. Highlights: First comprehensive systematic review on the quantity of Malathion, Diazinon and Chlorpyrifos in Vegetables. 22 articles containing 37 data reports underwent the meta-analysis. Rank in order of mean concentration was as follows: Diazinon > Chlorpyrifos > Malathion. Non-carcinogenic risks due to Malathion, Diazinon and Chlorpyrifos ingesting in Vegetables. Considerable non-carcinogenic risk in the consumer's vegetables was not observed (HQ < 1).